Peningkatan Laba Usaha melalui Edukasi Manajemen Persediaan dengan Aplikasi Koperasi Berbasis Android - I Gusti Ketut Agung Ulupui; Yunika Murdayanti; Siti Fatimah Zahra (Jurnal Pengabdian Pada Masyarakat, 2021)
INCREASING BUSINESS PROFIT THROUGH INVENTORY MANAGEMENT EDUCATION WITH ANDROID-BASED COOPERATIVE APPLICATIONS. This community service activity aims to understand cooperative managers and SMEs in managing their inventory records with digital technology. Generally, cooperative management becomes ineffective and inefficient and sometimes high inventory costs arise. The purpose of proper management is to minimize operational costs to a minimum so that it will optimize company performances. In overcoming this, cooperatives have the opportunity to continue to develop in the era of digitalization because business actors must collaborate and work together to survive and to develop their businesses and must be accompanied by creativity and innovation to organize organizations and business strategies by optimizing the application of digital technology. This method of implementing Community Service is carried out online through the zoom meeting application with cooperative/SMEs management participants and in collaboration with the Cooperative, SMEs and Trade sub-offices and is supported by Jakpreneur. The implementation of this activity was carried out for 1 day through a lecture approach method on training materials, practice and training discussion on inventory recording using an android-based financial note application. The achievement of the results of this activity is the resulting increase in the competence of cooperative and SMEs members which aims to be prepared as strong entrepreneurs, capable of starting businesses and being able to utilize information technology as a business opportunity to build relatively easy networks. Information technology has been proven to provide the opportunity to build a business efficiently while providing a reasonable profit.